SDS-dependent cleavage of nuclear DNA into high molecular weight DNA fragments: a signal to the engagement of apoptosis? - Solov'yan, V.T. (Биополимеры и клетка, 1997)
In this paper we employed an extraction of the cells with high concentration of sodium chloride (a procedure commonly used for preparation of histone-depleted nuclei) to investigate the genesis of nuclear DNA degradation during apoptosis. We demonstrated that apoptosis in primary culture of murine thymocytes and in continuously growing Swiss 3T3 fibroblasts is associated with progressive disintegration of nuclear DNA into high molecular weight (HMW) DNA fragments of about 50–150 kb followed by the development of oligonucleosomai DNA ladder. In apoptotic cells both HMW DNA cleavage and internucleosomal DNA fragmentation can be detected cither by cell treatment with ionic detergents (SDS) or by extraction with high concentration of sodium chloride. However, at the early stage of apoptosis only SOS-detected HMW-DNA cleavage can be observed which precedes the sodium-chloride-detected nuclear DNA degradation. SDS-detected but not sodium-chloride-detected formation of HMW-DNA fragments occurs in apoptotic cells as early as before detachment. It may be observed also in nonapoptotic cells after they reach t/ic confluent state and is reversible. On the basis of obtained results it is possible to suggest thai SDS-detected HMW-DNA cleavage represents a physiological reaction of alive cells that accompanies an early commitment step of apoptosis.